A cis-acting element in the promoter region of the murine c-myc gene is necessary for transcriptional block. - Miller, H (1989)
A block to elongation of transcription has been shown to occur within the first exon of the human and murine c-myc genes. The extent of this block was found to vary with the physiological state of cells, indicating that modulation of the transcriptional block can serve to control the expression of this gene. To determine which sequences are required in cis for the transcriptional block, we generated a series of constructs containing various portions of murine c-myc 5'-flanking and exon 1 sequences. We established populations of HeLa and CV-1 cells stably transfected with these constructs. The transcription start sites were determined by S1 nuclease mapping analysis, and the extent of transcriptional block was measured by nuclear run-on transcription assays. Our results demonstrate that at least two cis-acting elements are necessary for the transcriptional block. A 3' element was found to be located in the region where transcription stopped and showed features reminiscent of some termination sites found in procaryotes. A 5' element was positioned between the P1 and P2 (C. Asselin, A. Nepveu, and K. B. Marcu, Oncogene 4:549-558, 1989). Removal of the more 3' binding site abolished the transcriptional block.